2018
DOI: 10.5194/jsss-7-69-2018
|View full text |Cite
|
Sign up to set email alerts
|

Granular metal–carbon nanocomposites as piezoresistive sensor films – Part 2: Modeling longitudinal and transverse strain sensitivity

Abstract: Abstract. Granular and columnar nickel-carbon composites may exhibit large strain sensitivity, which makes them an interesting sensor material. Based on experimental results and morphological characterization of the material, we develop a model of the electron transport in the film and use it to explain its piezoresistive effect. First we describe a model for the electron transport from particle to particle. The model is then applied in Monte Carlo simulations of the resistance and strain properties of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…If strain is applied transverse to the current direction, the transverse detour-components of the conduction paths are strained as well, resulting in a resistance change with a transverse gauge factor k T . For a further analysis and modeling, we refer to our associated paper by Schwebke et al (2018).…”
Section: Longitudinal and Transversal Gauge Factorsmentioning
confidence: 99%
“…If strain is applied transverse to the current direction, the transverse detour-components of the conduction paths are strained as well, resulting in a resistance change with a transverse gauge factor k T . For a further analysis and modeling, we refer to our associated paper by Schwebke et al (2018).…”
Section: Longitudinal and Transversal Gauge Factorsmentioning
confidence: 99%
“…Granular thin-film SGs were manufactured by reactive sputter deposition of a NiCr − C thin film with a thickness of approximately 150 nm onto a polyimide foil with a thickness of 50 µm, according to Vollberg et al (2015). ) by applying different targets.…”
Section: Methodsmentioning
confidence: 99%
“…The path height (h) increases almost linearly with the scan repetitions, as does the SD. Tokarev et al (2003) showed that the ablation rate for polymers starts to decrease above a certain number of laser pulses, ultimately resulting in a spontaneous ablation stop. In our case, this leads to a reduced path height and proba-bly greater deviations above a certain number of scan repetitions.…”
Section: Laser Ablation Of Polyimide Structuresmentioning
confidence: 99%